GeoGebra in mathematics teaching - Papp-Varga, Zsuzsanna (Teaching Mathematics and Computer Science, 2008)
GeoGebra is a dynamic mathematics software which combines dynamic geometry and computer algebra systems into an easy-to-use package. Its marvel lies in the fact that it offers both the geometrical and algebraic representation of each mathematical object (points, lines etc.). The present article gives a sample of the potential uses of GeoGebra for mathematics teaching in secondary schools.